Application of the geostatistical Module ArcGIS for study of a geochemical field (on an example of a site Ponpel-Shor, Polar Ural) - V E Markov; А F Georgievskiy; L V Frolov (RUDN Journal of Engineering Research, 2010)
The maps of distribution of gold concentration and its elements-indicators on a surface were constructed for the site of gold mineralization Ponpel-Shor (Polar Ural). The application of the geostatistical Module ArcGIS allows to study anisotropic distribution of elements and confirms the assumption that the gold mineralization was formed in 2 stages.